O-004 The pattern of leptomeningeal collaterals on CT angiography is a strong predictor of good functional outcome in stroke patients with intracranial large vessel occlusion. (16th November 2010) - Lima, F; Furie, K; Silva, G; Lev, M; Camargo, É; Ay, H; Singhal, A; Harris, G; Halpern, E; Koroshetz, W; Smith, W; Yoo, A; et al.
Abstract : Background and purpose: The role of non-invasive methods in the evaluation of collateral circulation has yet to be defined. We hypothesized that a favorable pattern of leptomeningeal collaterals, as identified by CT angiography (CTA), correlates with improved outcomes. Methods: Data from a prospective cohort study at two university based hospitals where CTA was systematically performed in the acute phase of ischemic stroke were analyzed. Patients with complete occlusion of the intracranial internal carotid artery and/or the middle cerebral artery (segments M1 or M2) were selected. Leptomeningeal collateral pattern was graded as a three category ordinal variable (less, equal or greater compared with the unaffected contralateral hemisphere). Univariate and multivariate analyses were performed in order to define the independent predictors of good outcome at 6 months (modified Rankin Score (mRS) ≤2). Results: 196 patients were selected. Mean age was 69±17 years and median National Institutes of Health Stroke Scale (NIHSS) score was 13 (IQR 6–17). In the univariate analysis, age, baseline NIHSS, pre-stroke mRS, Alberta Stroke Programme Early CT Score, admission blood glucose, history of hypertension, coronary artery disease, congestive heart failure, atrial fibrillation, site of occlusion and collateral pattern were predictors of outcome. In the multivariate analysis, age (OR 0.95; 95% CI (0.93–0.98); p=0.001), baseline NIHSS (OR 0.75; 0.69–0.83; p<0.001), pre-stroke mRS (OR 0.41; 0.22–0.76; p=0.01), intravenous recombinant tissue plasminogen activator (OR 4.92; 1.83–13.25; p=0.01) and leptomeningeal collaterals (OR 1.93; 1.06–3.34; p=0.03) were identified as independent predictors of good outcome. Conclusion: Consistent with angiographic studies, leptomeningeal collaterals on CTA are also a reliable marker for good outcome in acute ischemic stroke patients presenting with large vessel occlusion. The acquisition of this information does not require any extra time or processing and may greatly assist in the selection of patients who are potential candidates for endovascular treatment.